The relationship between mental toughness and results of the Egyptian fencing team at the 9th All-Africa Games - Hagag, H.; Mahrousa, A. (Science, Movement & Health, 2014)
Purpose. Although sports science is well recognized for the past 40 years, sport psychologyis still considered as a new field. Sportspsychology concerns with both psychologicalfactors that influence participationand performance in sport andexerciseaswell aspsychological effects derived fromthem. The aim of the study was to investigate the relationship between mental toughness and results of the egyptian fencing team at the 9th all-africa games. Methods. Participants were members of the Egyptian Fencing federation who competed in the 9th All-Africa games held in Algiers, These athletes were competing in (3) weapons foil, epee, and saber events. The participants consisted of (22) fencers, (12) male and (10) female fencers. All of them participated in team competition , (18) fencers only participated in the individual competition. Results. The results were observed in the area of mental toughness when medallist and non medallists were analysed. The medallist displayed better self-confidence , better negative energy control and Visual - imagery control than the non medallist., the results suggested that the athletes with greater mental toughness were more likely to be selected into main team, to play in crucial competition , And Significant relationships between the Winning a medal and Self-confidence (. 58) , Visualization & Imagery(. 67) , Positive Energy Control (. 54) Conclusions.The mental toughness practice will be improvement the performance levels and the competations results in fencing .